SISTEM PENDINGINAN PERMUKAAN PANEL SURYA DALAM OPTIMALISASI KERJA PANEL SURYA DENGAN MONITORING INTERNET OF THINGS - Abdullah, Abdullah; Putri, Maharani; Iriani, Juli; Hulu, Fitria Nova; Cholish, Cholish (-, 2023)
The problem of the need for energy continues to increase, so a solution is needed in the form of alternative energy so that the problem of energy supply can be overcome. One of the solutions is through the utilization of solar energy by using solar panels with their photovoltaic properties. The problem is that solar panels must be optimized to work so that the output power can be optimal. The method in this study is the concept of a cooling system to overcome solar panels that are above their working temperature range where 1oC (starting from 25oC) will reduce the output power generated by solar panels by around 0.5% using two pumps placed on the east and west to flow water on the surface of the solar panels, so that the cooling system can move flexibly for the cooling process, where the condition of the cooling water is water that has been cooled using a combination of heatsinks and peltiers. From the test results it can be seen that the solar panel optimization system with a cooling system obtained a total solar panel output power of 140.64 Watts with an average output power of 14.06 Watts and a solar panel output power without a cooling system of 95.09 Watts with an average output power of 14.06 Watts. the average output power is 9.51 Watt with a percentage increase in the output power optimization system of 47.90% where all control and monitoring systems have worked well by integrating the Internet of Things.